2020
DOI: 10.24018/ejdent.2020.1.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress Levels in Pakistani Dental Students During COVID-19 Lockdown

Abstract: Objective: The objective of this study is to assess the stress levels of Pakistani dental students through an established stress assessment tool during lockdown for COVID-19 pandemic. Materials and methods: A cross-sectional quantitative study using a self-administered, voluntarily filled online questionnaire was conducted on undergraduate dental students from first to fourth (Final) years of dental institutes across Pakistan, accredited by the Pakistan Medical & Dental Council (PMDC). Study question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
16
3
Order By: Relevance
“…In one of such studies almost 68.5% healthcare workers dealing with COVID patients reported moderate to severe stress (22). Almost 53.5% of dental students were found to be suffering from severe stress in another study (23). To the best of our knowledge, there is hardly any literature available to evidence perceived stress levels of the general population of Pakistan amidst the rst wave of COVID-19, however considering alarming levels of moderate to severe stress in students and healthcare professionals, it is likely to speculate high levels of stress in the general population as well.…”
Section: Introductionmentioning
confidence: 96%
“…In one of such studies almost 68.5% healthcare workers dealing with COVID patients reported moderate to severe stress (22). Almost 53.5% of dental students were found to be suffering from severe stress in another study (23). To the best of our knowledge, there is hardly any literature available to evidence perceived stress levels of the general population of Pakistan amidst the rst wave of COVID-19, however considering alarming levels of moderate to severe stress in students and healthcare professionals, it is likely to speculate high levels of stress in the general population as well.…”
Section: Introductionmentioning
confidence: 96%
“…48 However, a higher proportion was reported in dental students from Pakistan (96.9%) and nursing students (96.01%) in Pune. 46 , 49 The potential reasons for such variability may be that (1) the severity and isolation modes of COVID-19 prevention and control vary during the different survey times and locations and (2) the characteristics of the investigation population are different. For instance, studies revealed that dental and nursing students experienced higher PS due to early practice stage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted in Pakistan 13 14 and Saudi Arabia 15 to assess stress levels in dental and medical students. However, there is scarce literature regarding the psychological well-being of health sciences students.…”
Section: Introductionmentioning
confidence: 99%